Instagram as a Da’wah Medium for Al-Hasany Foundation Islamic Boarding School - Nasikhul Amin; Moch. Agung Lukman Septiansyah; M. Havy Sa'dullah; Syaifuddin Syaifuddin (Fakultas Dakwah UIN Saizu Purwokerto, 2022)
Social media expands the volume of information for each individual so that it holds power over control. Human interaction through online media is not limited by time and space, as long as the user is connected to an internet connection. Unlimited interaction is a reason for an Islamic boarding school manager to create a @alhasanymedia Instagram account. This study explores the use of Instagram by Al-Hasany Islamic boarding school for da’wah. The research uses a qualitative field method, the research procedure assembles descriptive data of interview or written word sequences from the observed people, and this approach is directed at the individual setting in a holistic (whole) manner. In qualitative research, the author becomes an essential instrument (human instrument) to establish the focus of the research, find and select informants as the data source, collect data, assess data quality, analyze data, interpret data and make conclusions on the findings. The results of this study show that the Instagram account @alhasanymedia has contributed to Islamic boarding school as an educational institution which includes the media of da’wah, information, blessing, promotion, nostalgically, and documentation for pesantren and graduates of Al-Hasany Sumber Islamic boarding school, parents and Abituren.